Oscillation of Nonlinear Differential Equations with Advanced Arguments (Baghdad Science Journal, 2008)
This paper is concerned with the oscillation of all solutions of the n-th order delay differential equation . The necessary and sufficient conditions for oscillatory solutions are obtained and other conditions for nonoscillatory solution to converge to zero are established.